Title Economic Performance and Efficiency of Traditional Milkfish Pond Farming in Coastal Ponds of Sungai Undang Village, Seruyan Regency - Leni Handayani; Wahyuni; Sartika Pakpahan; Arizal Nur Hardiansyah (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2026)
Traditional milkfish pond farming represents and importan livelihood source for coastal communities, however, empirical information regarding income level and business efficiency in low input production systems remains limited. This study aimed to analyze productions cost s, revenue, income and economic efficiency of traditional milkfish farming in Sungai Undang village, Seruyan regency. A quantitatif survey approach was applied to 100 farmers selected using snowball sampling during one production cycle in 2025. Date were analyzed descriptively through the calculation of total cost, total revenue, income and the revenue cost ratio (R/C). The results showed an average production 0f 625 kg per cycle, generating an income of IDR 2.950.000 per cycle and an R/C ratio of 1,23, indicating that the business remains financially feasible with moderate efficiency. Most farmers were classified into feasible categories with limited profit margins. This condition is associated with high stocking density combined with reliance on natura feed, and low input fond management, resulting in suboptimal biological productivity but reduced production costs. These findings highlight  the role of traditional milkfish farming as a relatively stoble income source for coastal households and emphasize the need for improved simple technical management to enhance production performance and economic and efficiency.